The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13153260
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids and Calcium Oxide Grafted with Allylmalonic Acid Applied to Support the Peroxide Crosslinking of an Ethylene–Propylene Copolymer

Abstract: Nanosized calcium oxide (CaO) featuring a surface grafted with allylmalonic acid (ALA) was used to increase the efficiency of the peroxide crosslinking of an ethylene–propylene copolymer (EPM) filled with silica nanoparticles. In this study, 1-butyl-3-methylimidazolium ionic liquids (ILs) with different anions were applied to improve the dispersion of CaO/ALA and silica nanoparticles in the EPM copolymer, as well as to catalyze the interfacial crosslinking reactions. In this article, we discuss the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Toward this dilemma, many efforts have been made, including silane coupling agents [110], physical coating [111], ionizing radiation [112], chemical reactions [113], and macromolecular functionalization [114] methods. With the development of ionic liquid-modified nanofiller technology, many studies have reported that ILs could improve silica dispersion within matrix materials and enhance the interfacial bond strength [39,40,95,115].…”
Section: Silicamentioning
confidence: 99%
“…Toward this dilemma, many efforts have been made, including silane coupling agents [110], physical coating [111], ionizing radiation [112], chemical reactions [113], and macromolecular functionalization [114] methods. With the development of ionic liquid-modified nanofiller technology, many studies have reported that ILs could improve silica dispersion within matrix materials and enhance the interfacial bond strength [39,40,95,115].…”
Section: Silicamentioning
confidence: 99%